Industrial trial of high-quality all green sizes composed of soy-derived protein and glycerol. (1st November 2016) - Xu, Helan; Yang, Maiping; Hou, Xiuliang; Li, Wei; Su, Xuzhong; Yang, Yiqi
Abstract: All-green textile sizes with satisfactory weaving performance and biodegradability were developed from soy protein and glycerol, two major byproducts from soy-based biodiesel production. Polyvinyl alcohol has long dominated textile sizing chemical market due to its excellent sizing performance, despite its non-biodegradability. Efforts have been devoted to replace polyvinyl alcohol for a more sustainable textile industry. Recently, substitute size developed from soy protein after using high amount of petro-based triethanolamine showed acceptable sizing properties. However, triethanolamine was not an eco-friendly additive, due to its petroleum origin and non-biodegradability. In this research, glycerol was used to plasticize soy protein to develop all-green soy size. Glycerol interrupted hydrogen bonds in the soy globulin, allowing them to extend in the films. Resultantly, the soy size films possessed high stretchability and work of rupture. Lab-scale experiments and industrial weaving proved that the all-green soy size had similar or better weaving performance and remarkably better degradability, comparing to polyvinyl alcohol and triethanolamine plasticized soy protein size. For the first time, a possible logarithmic relationship was found between work of rupture of the size film and relative weaving efficiency. Graphical abstract: Highlights: Industrial trial showed all-green sizes had weaving performance similar to PVA. All-green textile sizes from soy protein and glycerol were readily biodegradable. Effect of size film tensile property on weaving was quantified for the first time. Glycerol was suitable for industrial use as a low-cost byproduct of biodiesel.